Understanding Immunology - Wood, Peter (Pearson Education, 2010)
A straightforward introduction to Immunology, which helps students focus on the key concepts which explain why the immune system functions as it does - finding a path through the complexity and jargon which can often be daunting for students. This new edition has been thoroughly updated to underline the changes in this fast-moving field.